Wychowanie obywatela w polskich reformach szkolnych... - Bartnicka, Kalina (Horyzonty Wychowania, 2017)
Since the end of the 1730s until the collapse of the Republicof Poland, we can observe a long-lasting process of transformationsin the organisation and the scope of youth education. The changes resulted from political premises. Their aim was to improve the condition of education in order to bring up citizenscapable of conducting the essential political and economical reforms in the state. The process was started by a Piarist Stanisław Konarski and his associates. Established in 1740 in Warsaw, an elitist and exclusive boarding school, resembling the academy for nobility, Collegium Nobilium, presented modernised traditional teaching and educational programmes. The children of magnates, i.e. future social and political elite of the state, were educated here. The concept of educational ideal was worked out and disseminated by Konarski in his well-known Speech how to bring up an honest man and good citizen since early youth (1750). The emphasis was put on moral and political education of the learned speakers and politicians. The experiences were used during the reform of public Piarist schools in the Crown (1750-1753). The reformist experiences and Piarist conceptions gave rise to the discussion about the need for and the scope of educational reforms in Poland as well as the propagation of the idea of improving the Republic of Poland through educational reform. The next stage of experiences concerning civic and patriotic education through modernisation and secularisation of school curricula was the establishment and activity of the Knight’s School of the Cadet Corps founded by king Stanisław August Poniatowski in Warsaw in 1765. It educated military and office cadres and was characterised by a very emotional educational atmosphere and modern encyclopaedic general education programme